Synthesis, structure and electrochemistry of new diferrocenyl pyridine derivatives - Wang, Ya-Qi; Han, Li-Min; Suo, Quan-Ling; Zhu, Ning; Hao, Jian-Min; Xie, Rui-Jun (Polyhedron, 2013)
Four diferrocenyl pyridine derivatives were synthesized via [2+2+2] cycloaddition reaction using FcCCH and PhCN or CH3CN as reactants, CpCo(CO)2 or Co2(CO)6(μ2-η2-FcCCH) as a catalyst. Four diferrocenyl pyridine derivatives, 4,6-diferrocenyl-2-phenylpyridine (1), 3,6-diferrocenyl-2-phenylpyridine (2), 4,6-diferrocenyl-2-methylpyridine (3) and 3,6-diferrocenyl-2-methylpyridine (4) were synthesized via dicarbonylcyclopentadienylcobalt or Co2(CO)6(μ2-η2-ferrocenylacetylene) mediated [2+2+2] cycloaddition reaction and characterized by FT-IR, NMR, MS, CV, elemental analysis and X-ray single crystal diffraction analysis (1, 2, 3). Compounds 1, 2, 4 are new diferrocenyl pyridine derivatives and the molecular structures of 1, 2, 3 have been determined for the first time. It has been shown that cobalt-mediated [2+2+2] cycloaddition reaction is an efficient, simple new method to prepare diferrocenyl pyridine derivatives. The electrochemistry results reveal that the electronic communication between the two nonequivalent ferrocenyl units in 1–4 is electrostatic interactions.